The Impact of Aging on the Quality of Sperm in White Rats (Rattus Norvegicus) Wistar Strain - Widiastini, Luh Putu; Karuniadi , I Gusti Agung Manik; Tangkas , Made (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Due to the reproductive aging process, the testes, epididymis, and other reproductive organs gradually lose all their physiological capabilities. This study aimed to determine the effect of aging on the sperm quality of Wistar rats (Rattus Norvegicus). The research design is quantitative and descriptive. This study used white male rats (Rattus norvegicus) of the Wistar strain aged 19–20 months. The number of samples was 18 individuals, with a purposive sampling technique following the inclusion and exclusion criteria. Mice were put to sleep on the seventh day, then the cauda epididymis and testes were separated, and a media container was used to accommodate them. The spermatozoa produced were then examined for their motility, morphology, and viability. The results showed that the range, mean, and standard deviation of progressive motility of spermatozoa was 5.83%, 217% ± 1.87%, normal morphology was 39.17%, 61.6% ± 9.57%, and spermatozoa viability was 19.50%, 74.6 ± 5.83%. There was a progressive decrease in motility, but morphology was expected, and spermatozoa viability was within normal limits. This study concludes that aging affects spermatozoa motility, but the morphology and viability of spermatozoa are still within normal limits. Future studies should do genetic analysis to determine how hereditary factors affect sperm quality in aged white rats and compare the results to those of young rats to identify changes in sperm quality.